Inspire Challenge Award: Pest and disease monitoring by using artificial intelligence - CGIAR Platform for Big Data in Agriculture (2018)
The project aimed to radically transform pest and disease monitoring by using artificial intelligence (AI), advanced sensor technology and crowdsourcing capable of connecting the global Ag community to help smallholder farmers.